Daily care of urgency and emergency in rural community (Research, Society and Development, 2020)
Objective: Write the care performed by residents in urgent and emergency cases in a rural community. Method:  This is an exploratory and descriptive research, of a qualitative nature. In which 42 adult residents were subjected, with the closing of a sample performed by semi-structured interview and saturation. Data analysis was performed by central id analysis. Results:  The research followed with women, mostly self-declared brown, aged 23 to 87 years, with completed 2nd degree, living in stable union and unemployed. Twenty-one types of urgent and emergency situations were evidenced, of which, in general, the most frequent were: hypertensive crisis, neurovascular disorders and signs and symptoms. Among the varied care performed by the participants were, oral medication use, Cardiopulmonary Resuscitation, inhalation and topical use of alcohol and herbs, intake of water with sugar and tea, as well as verification of vital signs were found. Conclusion:  Despite the challenges faced by the community, residents demonstrate a great deal of welcome and willingness to learn about the proper care. Being very receptive with actions that enhance access and accessibility to the health service.